Rasgando o véu: conservadorismo e antifeminismo em Sorocaba - Garcia, Priscila Dantas da Costa (Universidade Federal de São Carlos, 2021)
Antifeminisms can be understood as opposition to feminisms, and they are related to conservatism, religious fundamentalism, and the growing electoral expression of new right parties on the world stage. This research makes use of content analysis as a method and has as its main objective to investigate the articulations of antifeminisms and the way in which antifeminist actors uses of discursive strategies to invalidate achievements and expansion of legal rights related to feminist struggles. Therefore, will be used posts from pages on social networks related to the new right in Sorocaba, from 2018 to 2021, considering that this period is important in the history of the construction of a revamped right and the consequent articulation of antifeminism in Brazil. Images, videos and comments from the profiles affiliated to the pages will be taken into account, bearing in mind the ethical particularities of Internet research. The growing use of the internet as a way of disseminating conservative ideas makes it important to study virtual scenarios and understand the articulation of antifeminist actors in this vehicle. In the data’s analysis obtained from the field, we could apprehend the existence of the following categories: criticism of "gender ideology", moral panic and broaching pedofilia and abortion, the supposed "vagrancy" of people from the progressive field, the presumed association of progressive people with “dirt”, the connection of progressive people with madness or drug use, the critique of new masculinities. The research perceived the discourse associated with religious values, male domination and heterocisnormativity as an appeal for electoral representation. Frequently the mockery and psychopathologization strategies to falsify feminist discourses and rights achievements related to progressive agendas.
Unveiling: conservatism and antifeminism in Sorocaba
Keywords: Feminismo; Feminism; Gênero; Gender; Conservadorismo; Conservatism; Antifeminismo; Antifeminism; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL